Anomalies in VLF radio signals prior the abruzzo earthquake (M=6.3) on 6 april 2009 - Rozhnoi, A; Solovieva, M; Molchanov, O; Schwingenschuh, K; Boudjada, M; Biagi, PF; Maggipinto, T; Castellana, L; Hayakawa, M.; ERMINI, ANITA (Natural Hazards and Earth System Sciences, 2009)
The VLF/LF radio signals method for studying preseimic activity is applied to the Abruzzo earthquake (MCombining double low line6.3, 6 April 2009). The data collected by three receivers located in Moscow (Russia), Graz (Austria) and Bari (Italy) at about 3000 km, 1000 km and 500 km from the epicenter were used. The signals received from the Sardinia (20.27 kHz) and the Sicily (45.9 kHz) transmitters, both located in Italy, were compared with those received from the Iceland (37.5 kHz), the Great Britain (19.58 kHz) and the Germany (23.4 kHz) transmitters. The propagation paths of the two Italian transmitters cross the epicentral area (seismic paths) unlike the paths of the other three signals (control paths). Using two different analyses, that are the study of the night-time signal and the research of shifts in the evening terminator times, clear anomalies were revealed 2ĝ€"8 days before the occurrence of the Abruzzo earthquake in the seismic paths, while no anomalies have been found in the control paths.